2021
DOI: 10.1097/cji.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of an IDO-1 Inhibitor (LY3381916) as Monotherapy and in Combination With an Anti-PD-L1 Antibody (LY3300054) in Patients With Advanced Cancer

Abstract: LY3381916 is an orally available, highly selective, potent inhibitor of indoleamine 2,3-dioxygenase 1. This study explored the safety, tolerability, pharmacokinetics, pharmacodynamics, and antitumor activity of LY3381916 monotherapy and in combination with a programmed death-ligand 1 (PD-L1) inhibitor (LY3300054) in patients with advanced solid tumors. During dose escalation, patients received escalating doses of LY3381916 at 60-600 mg once daily (qd) and 240 mg twice daily in monotherapy (n = 21) and in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In addition to the aforementioned IDO1 inhibitors, some other small molecules or vaccines have fared clinical development, including LY3381916, MK-7162, IO102 and KHK2455, alone or combined with ICI. For example, LY3381916 is a highly selective and potent inhibitor of IDO1 that was evaluated alone or combined with a PD-L1 blocker in patients with advanced or metastatic cancer (102). No clear clinical activity was detected, thus warranting further studies.…”
Section: Clinical Development Of Ido1 Inhibitorsmentioning
confidence: 99%
“…In addition to the aforementioned IDO1 inhibitors, some other small molecules or vaccines have fared clinical development, including LY3381916, MK-7162, IO102 and KHK2455, alone or combined with ICI. For example, LY3381916 is a highly selective and potent inhibitor of IDO1 that was evaluated alone or combined with a PD-L1 blocker in patients with advanced or metastatic cancer (102). No clear clinical activity was detected, thus warranting further studies.…”
Section: Clinical Development Of Ido1 Inhibitorsmentioning
confidence: 99%
“…6,7 Clinical trials with apo-IDO1 inhibitors, having a different inhibition mechanism from epacadostat, are ongoing. 4,8,9 In addition to its enzymatic activity, IDO1 also displays a signaling activity mediated by two immunoreceptor tyrosinebased inhibitory motifs and a post-transcriptional regulatory site. 2 IDO1's interaction sites with Src homology 2 domain phosphatases (SHPs), 10 phosphoinositide 3-kinases (PI3Ks), 11 and suppressor of cytokine signaling 3 (SOCS3) 12 are all localized in the small domain and are distinct from the enzymatic active site in the large domain (Figure 1A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a key regulator of immune responses, IDO1 is an important therapeutic target for diseases that involve pathological immune escape, such as cancer. , Numerous small-molecule IDO1 inhibitors have been published since the discovery of the implication of IDO1 in tumoral immune resistance, and several compounds entered clinical evaluation. , However, despite compelling preclinical and early clinical data, a phase 3 clinical trial of the IDO1 inhibitor epacadostat in combination with pembrolizumab (ECHO-301) failed to increase the overall and progression-free survival when compared to pembrolizumab alone . Potential reasons for the negative outcome of this clinical trial and possible solutions have been suggested, for example, intratumoral kynurenine level monitoring in combination with the use of more potent and more selective IDO1 inhibitors or dual IDO1–tryptophan 2,3-dioxygenase (TDO) inhibitors. , Clinical trials with apo-IDO1 inhibitors, having a different inhibition mechanism from epacadostat, are ongoing. ,, …”
Section: Introductionmentioning
confidence: 99%
“…We speculate that this might be related to PD-1/PD-L1 inhibitor resistance in some patients with NSCLC ( Lei et al, 2020 ). This suggests that inhibiting the tryptophan-kynurenine pathway through the administration of indoleamine-2,3-dioxygenase inhibitors may benefit NSCLC patients who are resistant to PD-1/PD-L1 inhibitors ( Kotecki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%